PENGARUH PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PT. FUJI KINZOKU INDONESIA PADA DEPARTEMEN QUALITY CONTROL - Ayuni, Putri; Junengsih, Junengsih; Army, Widya Lelisa (JURNAL ILMIAH EDUNOMIKA, 2024)
Increasingly fierce competition in the era of globalization requires human resources (HR) to develop themselves proactively. The influence of work quality based on the welfare and justice provided by the company, the influence of work quality in the absence of career development within the company also triggers a decline in worker morale and quality. PT. Fuji Kinzoku Indonesia is engaged in manufacturing in the automotive industry, producing components for four-wheeled or more motorized vehicles. There is a phenomenon at PT. Fuji Kinzoku Indonesia regarding career development where employee recruitment is done through outsourcing which sometimes causes more harm to employees because of the large number of deductions from employee salaries. This research aims to examine the influence of career development on employee performance at PT. Fuji Kinzoku Indonesia, especially in the Quality Control Department. This research uses quantitative methods with data collection techniques through questionnaires to 45 employees of the Quality Control Department at PT. Fuji Kinzoku Indonesia. The results of the validity and reliability tests show that this research instrument is valid and reliable. There is a positive influence between career development and employee performance. The results of the analysis show that an increase in career development contributes to an increase in employee performance. In 2021, when companies reduced new recruitment during the COVID-19 pandemic, there was an increase in the status of contract employees to permanent employees. Therefore, career development has a positive impact on employee performance at PT. Fuji Kinzoku Indonesia.